The 3D-Language Acquisition Test and the Mentally Retarded - Pillai, Kamalini (Journal of All India Institute of Speech and Hearing)
The 3D-LAT was administered to 45 moderately retarded children, to study their performance on it and to make inferences regarding the language behaviour of retarded children.